Prophylactic and curative anti-ulcerative colitis activity and the possible mechanisms of action of some desert plants. (8th May 2014) - El-Meligy, Reham M.; Awaad, Amani S.; Soliman, Gamal A.; Bacha, Abir B.; Alafeefy, Ahmed M.; Kenawy, Sanaa A.
Abstract: The aim of the present study was to evaluate both prophylactic and curative anti-ulcerative colitis activity and the possible mechanism of action of seven desert plant extracts. Seven desert plants from different families; Conyza dioscoridis (L.) Desf. (Asteraceae), Euphorbia hirta L. (Euphorpiaceae), Origanum syriacum L. and Salvia lanigera L. (Lamiaceae), Sisymbrium irio L., Solanum nigrum Linn. (Solanaceae) and Solenostemma arghel (Del.) Hayne. (Asclepiadaceae) were separately evaluated at three doses (125, 250, and 500 mg/kg) using the acetic acid-induced colitis model. The investigated extracts possessed prophylactic and curative anti-ulcerative colitis activities in a dose-dependent manner, where Salvia lanigera (87.9) and Solenostemma arghel (89.2) were the most effective extracts whereas the dexamesathone produced 68%. These extracts were further investigated for estimation of their mechanism of action. The in vitro potential radical (DPPH) scavenging activities of the investigated extracts were well supported with the reduction of colonic MDA content for both extracts. Suppression of the inflammatory mediator TNF-α and inhibition of both PLA2 and protease enzymes may play an important role in the anti-ulcerative colitis activities. The investigated extracts were safe for use up to 5 g/kg and the total alcohol extracts of Salvia lanigera and Solenostemma arghel (400 mg/kg for 35 d) showed no alteration on liver and kidney functions. Phytochemical screening of the investigated extracts revealed the presence of flavonoids, tannins, unsaturated sterols, and proteins which could be responsible for the activities.